Economics of Small Tea Farming System (STFS): An in-depth Study of North Bengal, India (Indian Journal of Extension Education, 2021)
The study was conducted to find out the pattern of labour engagement (both family and hired labour), price realization of different type of small tea growers and economic analysis of the small tea growing system. Small tea growers of Jalpaiguri and Uttar Dinajpur district of West Bengal were selected purposively. The present study mainly considered primary data for analysis and a small amount of secondary data was also collected from records of Confederation of Indian Small Tea Growers’ Association (CISTA) and Self-Help Group (SHG) registers. It has been found that there is a variation in price of green leaves in both districts and higher rates are observed in the month of March. SHGs with own processing units were found to fetch higher prices compared to other units because of their collective bargaining power, absence of middlemen and owing co-operative processing units. Number of such SHGs, with processing units were found in Jalpaiguri district whereas, Uttar Dinajpur district recorded no SHG with own processing units. The economic analysis also presented a clear picture about fixed and operational cost, gross return with or without dividend and benefit cost ratio.